Immunometabolism and Sepsis: A Role for HIF? - Fitzpatrick, Susan F. (Frontiers in Molecular Biosciences, 2019)
Metabolic reprogramming of innate immune cells occurs during both the hyperinflammatory and immunotolerant phases of sepsis. The hypoxia inducible factor (HIF) signaling pathway plays a vital role in regulating these metabolic changes. This review initially summarizes the HIF-driven changes in metabolic dynamics of innate immune cells in response to sepsis. The hyperinflammatory phase of sepsis is accompanied by a metabolic switch from oxidative phosphorylation to HIF-1α mediated glycolysis. Furthermore, HIF driven alterations in arginine metabolism also occur during this phase. This promotes sepsis pathophysiology and the development of clinical symptoms. These early metabolic changes are followed by a late immunotolerant phase, in which suppressed HIF signaling promotes a switch from aerobic glycolysis to fatty acid oxidation, with a subsequent anti-inflammatory response developing. Recently the molecular mechanisms controlling HIF activation during these early and late phases have begun to be elucidated. In the final part of this review the contribution of toll-like receptors, transcription factors, metabolic intermediates, kinases and reactive oxygen species, in governing the HIF-induced metabolic reprogramming of innate immune cells will be discussed. Importantly, understanding these regulatory mechanisms can lead to the development of novel diagnostic and therapeutic strategies targeting the HIF-dependent metabolic state of innate immune cells